GARCÍA DONCEL, M. - ROMERO, JOSEP M. (eds.), Actualitat de Teilhard de Chardin - Sequeiros, L. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
(Fundació Joan Maragall, Barcelona, 2008, Editorial Cruïlla). 186 pp. ISBN: 976-86-661-2027-2.